PROCESS FOR PRODUCING AN ELECTROCHEMICAL CELL, AND ELECTROCHEMICAL CELL PRODUCED BY THE PROCESS - NIKOLOWSKI KRISTIAN; KUSNEZOFF MIHAILS; WOLTER MAREIKE; PARTSCH UWE; SCHILM JOCHEN; FREYTAG CHRISTIAN (2019)
The invention relates to a process for producing an electrochemical cell, particularly a solid-electrolyte battery, wherein a paste or foil is applied to each of the opposing surfaces of a solid electrolyte that form the respective anode and the respective electrode, and organic components within the pastes or foils are expelled in a heat treatment under an inert or reducing atmosphere. Subsequentto this, in a further stage, a fusional connection is produced by sintering between the anode and the solid electrolyte and between the cathode and the solid electrolyte. Here, the solid electrolyteis formed with an oxidic material conductive for lithium ions, the anode with a first lithium-containing chemical compound, particularly lithium titanate, and carbon, and the cathode with a second lithium-containing chemical compound, particularly a lithium metal phosphate, and carbon, to give a three-layer electrochemical cell construction devoid of organic components. 本发明涉及用于制造电化学电池、尤其固体电解质电池的方法，其中，将膏状物或片材应用于固体电解质的相对表面中的